American Economic Association Universal Academic Questionnaire Summary Statistics - E., Scott, Charles; J., Siegfried, John (American Economic Review, 2013)
American Economic Association Universal Academic Questionnaire Summary Statistics by Charles E. Scott and John J. Siegfried. Published in volume 103, issue 3, pages 678-82 of American Economic Review, May 2013